Da intervenção à solidariedade: caminhos para uma nova ordem mundial - Camera, Sinara (2008)
By the end of the 20th century and the beginning of the 21st century the late and insufficient acts of the United Nations in its mission to keep peace and international security as well as the respect to human rights, seal and demonstrate its inability to give quick answers to extreme situations. The present study aims to investigate the possible reformulations occurred in the Humanitarian Intervention model throughout the investigated period, in order to disclose the factors (facts, theories, practices) that clarify these changes as well as to discuss the possible ways for the construction of new spaces, dialogic, collaborative and solidary, throughout a humanitarian intervention, in this re-structuring process. This period also shows strong disagreement amongst the defenders of the intervention for humanity reasons and the sponsors of the sovereignty as intangible principle. There is not a consensus about the existence of a right or duty of humanitarian interference, for whom it must be done and the moment to accomplish it. On the other hand, there is a consensus regarding the inefficacy of the logic used to implement an intervention for humanitarian reasons. The unsuitability of the actions seen so far, and the selectivity criteria (or lack of them), show the farness between the means and ends of the humanitarian intervention as well as the need of creating clear rules for its practice. So, the protection responsibility theory arises, whose purpose is to regulate the international collective acting in the armed interventions. However, considering the purely technical aspects, it seems that the operational principles brought by the new theory are the biggest differential in relation to the classical humanitarian intervention. The modus operandi of these interventions has always been strongly criticized, that is, the excesses committed by troops during occupation, the lack of parameters for the action of multinational troops (with formation and distinct orientations), the disproportion in the use of power, promote debates about the farness between the means and ends in humanitarian interventions. It is important to mention that the human element needs to be present during all military action (preparatory, successive and posterior). Finally, only when this element is, in fact, considered, will the means and ends converge towards a common point, which is the protection of every person s human rights in the State territory under intervention. The people who compose the States government make the difference, heating the cold reason of the State, giving opportunity to solidary actions and, therefore, working with distinct proposal possibilities by traditional mechanisms of conflict resolution. With the logic of power that rules international relations, the will of many men and women still resists within the governments, the academy, and civil society, which have put a great deal of effort on a new world order, showing new ways and new solidarity spaces in intervention situations.